A randomized, 5‐arm dose finding study with a mite allergoid SCIT in allergic rhinoconjunctivitis patients. Issue 7 (29th March 2016) - Pfaar, O.; Nell, M. J.; Boot, J. D.; Versteeg, S. A.; van Ree, R.; Roger, A.; Riechelmann, H.; Sperl, A.; Oude Elberink, J. N. G.; Diamant, Z.; Bachert, C.
Abstract: Background: The safety and tolerability of a mite allergoid subcutaneous allergen immunotherapy (SCIT) product was previously established. The aim of this study (EudraCT number: 2011–000393–61) was to find the optimally safe and effective allergoid dose by evaluating several dosages in patients with house dust mite (HDM)‐induced allergic rhinoconjunctivitis (ARC) using a titrated nasal provocation test (TNPT). Methods: In total, 290 adult ARC patients (148 females; 142 males) with established HDM allergy and with a positive TNPT were randomized to receive placebo or mite allergoid SCIT 6667, 20 000, 50 000 or 100 000 AUeq/ml for 12 months. Patients were updosed weekly, followed by monthly maintenance dosing. The primary study endpoint comprised the clinical response to TNPT after 12 months of treatment. Secondary endpoints included response to TNPT after 6 months, PNIF measurements, symptom and medication scores during the last 8 weeks of treatment, serum immunoglobulins and safety assessments. Results: After 12 months, a dose–response was observed showing statistically significant improvements in the TNPT with SCIT concentrations of ≥20 000 AUeq/ml, while no significantly different outcomes were reached after 6 months. Specific serum IgG and IgG4 levels were dose dependently increased. In the highest dose group, more treatment‐emergent adverse events were observed compared with the lower dose groups. Conclusion: In this mite allergoid SCIT dose finding study in HDM‐induced ARC, concentrations of ≥20 000 AUeq/ml showed both immunological effects and clinical efficacy in the TNPT compared with placebo. The risk–benefit ratio favours 20 000 AUeq/ml and 50 000 AUeq/ml strengths for further clinical development.